IgG4-related chronic sclerosing sialadenitis in a child with recurrent parotitis: a case report - Fabio Timeus; Mario Michele Calvo; Anna Maria Caci; Giorgio Oliviero Gallone; Federico Vittone (BMC, 2021)
Abstract Background IgG4-related disease (IgG4-RD) includes a group of immune-mediated diseases histologically characterized by lymphoplasmacytic infiltrate with a prevalence of IgG4-positive plasma cells, storiform fibrosis and obliterative phlebitis. Autoimmune pancreatitis, sialadenitis, dacryoadenitis and retroperitoneal fibrosis are the most frequent manifestations. IgG4-related sialadenitis usually affects submandibular glands and is very rare in children. Here we report the case of IgG4-related sialadenitis in a six-year-old patient previously diagnosed as juvenile recurrent parotitis. Case presentation A six-year-old patient was referred to our Centre for left parotid swelling of 4 × 3 cm, that was tender, soft in consistency, with overlying red and warm skin. His general condition was good but he was subfebrile; general examination revealed mild enlargement of left cervical lymph nodes. In the last 2 years he had had five episodes of parotitis, diagnosed by another pediatric Center as juvenile recurrent parotitis. On ultrasound examination the left parotid gland appeared enlarged, inhomogeneous, with a colliquative intraparotid lymph node and no evidence of sialolithiasis. Laboratory tests showed an increase of white blood cells and anti-VCA IgM and IgG positivity, with anti-EBNA e anti-EA I negativity. The patient was initially treated with oral antibiotics, but after 10 days the parotid became fluctuating, requiring surgical biopsy and drainage. Postoperative course was regular, with complete remission under oral antibiotic and steroid therapy. Microbiological tests, including cultures for aerobic and anaerobic bacteria, mycobacteria and Bartonella, were negative. Surprisingly, histology showed marked fibrosis and histiocytic and lymphoplasmacellular infiltrate with polyclonal plasma cells mostly expressing IgG4 immunoglobulins. Thus, the diagnosis of IgG4 related chronic sialadenitis in recurrent parotitis and recent EBV infection was made. Conclusions IgG4-related sialadenitis is very unusual in children. Histology plays a key role in diagnosis, considering that up to 30% of patients have normal serum IgG4 levels, as shown in our case. The lack of previous histological data makes it impossible to attribute our patient's previous episodes of parotitis to IgG4-RD, though it is a very consistent possibility.